LATE-AND POST-MIOCENE GEODYNAMIC EVOLUTION OF THE MESOGEA BASIN (EAST ATTICA, GREECE): CONSTRAINTS FROM SEDIMENT PETROGRAPHY AND STRUCTURES - Mposkos, E.; Krohe, A.; Diamantopoulos, A.; Baziotis, I. (Bulletin of the Geological Society of Greece, 2007)
In Attica, from the Miocene through the Quaternary, successive generations of detachment faults caused exhumation and denudation of Alpine HP rocks and – later on -formation of sedimentary basins. The Mesogea low angle detachment fault separates the HP rocks exposed at the southern flank of the Penteli Mtfrom the Late - post-Late Miocene Mesogea basin. Combined sedimentary-petrologic and structural analyses reveal the following: (i) Late Miocene sediments include material from unmetamorphosed source areas suggesting that, until then, parts of the HP rocks were buried under the (largely unmetamorphosed) Pelagonian nappe unit, (ii) Post-Late Miocene sediments exclusively contain clasts from high-P source areas and show downward bending of the layering that accommodates slip along a lis trie fault surface. Close to the Penteli Mt, within the post-Late-Miocene sediments gravity sliding-blocL· of metamorphic rocks occur. All this indicates post-Late Miocene activity along this detachment fault controlled rapid surface uplift/relief formation, denudation and fast erosion of HP rocks in the Penteli Mt.